Female Entrepreneurs Owning Small Businesses in the Agriculture Sectorin Comoros,Africa: Challenges Faced in the Conventional System - Asmaou Mohamed Bacha; Habeebullah Zakariyah; Syarah Syahira Mohd Yusoff; Rusni Hassan (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 22 Issue 2 Page (57–76)